2015
DOI: 10.5152/iao.2014.76
|View full text |Cite
|
Sign up to set email alerts
|

New Inflammation Parameters in Sudden Sensorineural Hearing Loss: Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio

Abstract: OBJECTIVE:The etiopathogenesis of sudden sensorineural hearing loss (SSNHL) is not clearly defined. Inflammation is being emphasized in its etiology. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are the parameters that show inflammation that can be obtained easily without additional cost. In this study, we aimed at delineating the relationship between SSNHL and the inflammation markers NLR and PLR. MATERIALS and METHODS:This study was performed with 102 patients diagnosed with SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
(32 reference statements)
1
17
0
2
Order By: Relevance
“…Higher neutrophil counts may be associated with inflammatory conditions. 8 The NLR is an inflammatory marker that has been studied in recent years for many diseases. The presence of an elevated NLR in SSHL demonstrated via the literature search.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher neutrophil counts may be associated with inflammatory conditions. 8 The NLR is an inflammatory marker that has been studied in recent years for many diseases. The presence of an elevated NLR in SSHL demonstrated via the literature search.…”
Section: Discussionmentioning
confidence: 99%
“…Less than 10 dB improvement in hearing level relative to the initial hearing level. 8 Systemic otorhinolaryngological examinations performed. Whole blood analysis results evaluated retrospectively.…”
Section: No Curementioning
confidence: 99%
“…Platelets interact with both leukocytes and endothelial cells, secrete chemokins and generate inflammatory lipids (12,13). The NLR and PLR serve as inflammatory biomarkers in diseases including Behcet's syndrome, Rheumatoid arthritis, sudden hearing loss, nasal polyposis, cardiovascular diseases and malignancy in all of which systemic inflammation is an important feature (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The MPV may be a new marker of inflammation in Behcet's syndrome, asthma, chronic obstructive pulmonary disease, arthritis (20,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that, the neutrophil to lymphocyte ratio (NLR), the mean platelet volume (MPV) and the platelet to lymphocyte ratio (PLR) are of diagnostic and predictive utility in systemic inflammatory disorders, cancer, cardiovascular diseases which may be used as diagnostic and prognostic indicators (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). These ratios have also been investigated as biomarkers of sudden idiopathic sensoryneural hearing loss and nasal polyposis (18)(19)(20). The aim of the present study was to examine the levels of complete blood count (CBC) parameters (Neutrophil, lymphocyte, platelets, MPV, NLR, and PLR) in patients with both perforated eardrums and dysfunctional eustachian tubes to determine which of these parameters might be reliable biomarkers of chronic otitis media prior to surgery, as inflammation is significant component of middle ear pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Повышение тромбоцитарно-лимфоцитарного отношения наблюдается при различных нарушениях периферического кровообращения, патологии коронарных артерий, некоторых злокачественных новообразованиях. Высокое нейтрофильно-лимфоцитарное отношение характерно для системного воспалительного процесса, являясь плохим прогностическим признаком [48]. Повышение нейтрофильно-лимфоцитарного отношения имеет место при различных заболеваниях сердечно-сосудистой системы, параличе Бэлла, почечной недостаточности, ИНСТ.…”
Section: теория микротромбообразованияunclassified